MicroRNAs Are Absorbed in Biologically Meaningful Amounts from Nutritionally Relevant Doses of Cow Milk and Affect Gene Expression in Peripheral Blood Mononuclear Cells, HEK-293 Kidney Cell Cultures, and Mouse Livers. Issue 10 (13th August 2014) - Baier, Scott R.; Nguyen, Christopher; Xie, Fang; Wood, Jennifer R.; Zempleni, Janos
Abstract: Background: MicroRNAs (miRNAs) regulate genes in animals and plants and can be synthesized endogenously. In milk, miRNAs are encapsulated in exosomes, thereby conferring protection against degradation and facilitating uptake by endocytosis. The majority of bovine miRNAs have nucleotide sequences complementary to human gene transcripts, suggesting that miRNAs in milk might regulate human genes. Objectives: We tested the hypotheses that humans absorb biologically meaningful amounts of miRNAs from nutritionally relevant doses of milk, milk-borne miRNAs regulate human gene expression, and mammals cannot compensate for dietary miRNA depletion by endogenous miRNA synthesis. Methods: Healthy adults (3 men, 2 women; aged 26–49 y) consumed 0.25, 0.5, and 1.0 L of milk in a randomized crossover design. Gene expression studies and milk miRNA depletion studies were conducted in human cell cultures and mice, respectively. For comparison, feeding studies with plant miRNAs from broccoli were conducted in humans. Results: Postprandial concentration time curves suggest that meaningful amounts of miRNA (miR)-29b and miR-200c were absorbed; plasma concentrations of miR-1 did not change (negative control). The expression of runt-related transcription factor 2 ( RUNX2 ), a known target of miR-29b, increased by 31% in blood mononuclear cells after milk consumption compared with baseline. When milk exosomes were added to cell culture media, mimicking postprandial concentrations of miR-29b and miR-200c, reporter gene activities significantly decreased by 44% and 17%, respectively, compared with vehicle controls in human embryonic kidney 293 cells. When C57BL/6J mice were fed a milk miRNA-depleted diet for 4 wk, plasma miR-29b concentrations were significantly decreased by 61% compared with miRNA-sufficient controls, i.e., endogenous synthesis did not compensate for dietary depletion. Broccoli sprout feeding studies were conducted as a control and elicited no detectable increase in Brassica -specific miRNAs. Conclusion: We conclude that miRNAs in milk are bioactive food compounds that regulate human genes.